2018
DOI: 10.1016/j.bja.2018.01.035
|View full text |Cite
|
Sign up to set email alerts
|

Does intranasal dexmedetomidine provide adequate plasma concentrations for sedation in children: a pharmacokinetic study

Abstract: Mean arterial plasma concentrations of dexmedetomidine in infants and toddlers approached 100 pg ml, the low end reported for sedative efficacy, within 20 min of an atomised intranasal administration of 1 μg kg. Doubling the dose to 2 μg kg reached this plasma concentration within 10 min and achieved almost twice the peak concentration. Peak plasma concentrations with both doses were reached within 47 min of intranasal administration, with an overall bioavailability of 84%.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
68
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(75 citation statements)
references
References 38 publications
6
68
1
Order By: Relevance
“…but lower than those after intramuscular and intravenous administration . According to the literature, the bioavailability of intranasally administered DEX is sufficient to warrant further investigation, and the median absolute bioavailability of intranasally administered DEX was reported to be 83.8% (69.5%‐98.1%) in children. We performed intranasal administration by nasal dropping, which is more convenient and quicker than the atomization method.…”
Section: Discussioncontrasting
confidence: 86%
See 1 more Smart Citation
“…but lower than those after intramuscular and intravenous administration . According to the literature, the bioavailability of intranasally administered DEX is sufficient to warrant further investigation, and the median absolute bioavailability of intranasally administered DEX was reported to be 83.8% (69.5%‐98.1%) in children. We performed intranasal administration by nasal dropping, which is more convenient and quicker than the atomization method.…”
Section: Discussioncontrasting
confidence: 86%
“…The intranasal route is an effective and quite comfortable way to administer DEX, especially in children with a fear of needles, and this route may be superior to intravenous or intramuscular administration. The plasma concentrations after intranasal administration were higher than plasma concentrations after oral and buccal administration . but lower than those after intramuscular and intravenous administration .…”
Section: Discussionmentioning
confidence: 92%
“…The bioavailability of intranasal dexmedetomidine using an atomizer has been reported to be 83.8% in children. 21 Furthermore, the mucosal atomization device used in this study delivers an atomized solution to the nasal mucosa that results in rapid absorption of the drug directly into the systemic circulation. Intranasal administration offers the potential of a less invasive and convenient approach to anesthetic premedication in children.…”
Section: Discussionmentioning
confidence: 99%
“…As animal studies have shown, drugs can be administered through the nasal cavity, which can effectively reduce first-pass elimination, and the drug can more efficiently enter the brain through the nervous olfactory system [8]. The overall bioavailability of DEX in children with intranasal administration was reported to be 84% [9]. The use of DEX alone in paediatric sedation provides adequate sedation [10,11].…”
Section: Introductionmentioning
confidence: 99%